1976
DOI: 10.1902/jop.1976.47.6.331
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gliding Tooth Contacts during Mastication

Abstract: Tooth gliding occurs frequently both in the opening (55.9%) and closing (60.5%) chewing strokes. The average glide length was 1 mm. Good occlusions could not be distinguished from poor occlusion on the basis of frequency and length of gliding contacts. The greater the component of lateral movement during the closing stroke, the greater the probability that gliding contacts would occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…Suit and coworkers showed that the greater lateral movements were during the closing stroke, the greater was the probability that gliding contacts would occur. 34 Given the importance of tooth contact during mastication, 3 it is possible that a more lateral path of closure leads to more efficient chewing produced by increasing the time of gliding occlusal contacts. Differences in cycle shape between better and poorer performers were also evident in the anteroposterior plane, with poorer performers exhibiting greater posterior movements.…”
Section: Discussionmentioning
confidence: 99%
“…Suit and coworkers showed that the greater lateral movements were during the closing stroke, the greater was the probability that gliding contacts would occur. 34 Given the importance of tooth contact during mastication, 3 it is possible that a more lateral path of closure leads to more efficient chewing produced by increasing the time of gliding occlusal contacts. Differences in cycle shape between better and poorer performers were also evident in the anteroposterior plane, with poorer performers exhibiting greater posterior movements.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gibbs et al 9 found that occlusal forces during swallowing and mastication are only approximately 40 per cent of maximal bite force. Suit et al 10 reported that tooth contact occurs on average for only 194 milliseconds during mastication and for 683 milliseconds during swallowing. Considering that the duration and magnitude of forces during bruxism are much greater than those during functional activity, it is more likely that parafunction would result in such a process rather than function.…”
Section: The Development Of the Concept Of Abfractionmentioning
confidence: 99%
“…Since tooth gliding contacts during the closing phase has an important role in the characteristic of the chewing cycle, 9,19 we selected the pathway when the reference point was positioned 0.5 mm below the intercuspal position on which tooth gliding contacts might occur for all subjects (Fig 4). As for the condylar point, the length of the condylar trajectory and the maximum velocity of condylar movement during the EMG bursts were calculated.…”
Section: Measurement Of the Mandibular Movementmentioning
confidence: 99%
“…Wilding 7 and Ikebe et al 8 also emphasized the association between occlusal contacts and masticatory performance. Moreover, Suit et al 9 described the importance of tooth guidance during mastication and Yamashita et al 10 concluded in their review article that tooth anatomy played an important role in the direction of jaw movement during mastication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation